2015
DOI: 10.1515/geochr-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Radial growth responses of Pinus halepensis Mill. and Pinus pinea L. forests to climate variability in Western Albania

Abstract: Abstract:In this study are presented chronologies of earlywood (EW), latewood (LW) and tree-ring widths (RW) of a Pinus halepensis (P. halepensis) and Pinus pinea (P. pinea) natural forest stand growing in western Albania. Bootstrapped correlations and pointer year analysis were combined in a dendroclimatological study to evaluate climate-growth relationships in both pine species as well as to assess the spatial outreach of our chronologies evaluating them with those of the same species from other Mediterranea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
5
11
0
1
Order By: Relevance
“…The above presented pattern of climate-growth relationship, namely the positive dominance of summer precipitation and negative impact of summer temperature was reported in other studies in Hungary on beech (Garamszegi & Kern, 2014) and on oak (Kern et al, 2013) and was observed many times on pine (Koprowski, 2012;Michelot, 2012;Panayotov et al, 2013;Levanič, 2015;Toromani et al, 2015) as well. However, we found a much unusual pattern also, which has never been observed in Hungary neither on pines nor on other species, but rare in the MJJ (May-June-July), JJA (June-July-August), SPR (March-April-May) and VGP (March-October) represent the combined periods, GWL shows groundwater data.…”
Section: Discussionsupporting
confidence: 76%
“…The above presented pattern of climate-growth relationship, namely the positive dominance of summer precipitation and negative impact of summer temperature was reported in other studies in Hungary on beech (Garamszegi & Kern, 2014) and on oak (Kern et al, 2013) and was observed many times on pine (Koprowski, 2012;Michelot, 2012;Panayotov et al, 2013;Levanič, 2015;Toromani et al, 2015) as well. However, we found a much unusual pattern also, which has never been observed in Hungary neither on pines nor on other species, but rare in the MJJ (May-June-July), JJA (June-July-August), SPR (March-April-May) and VGP (March-October) represent the combined periods, GWL shows groundwater data.…”
Section: Discussionsupporting
confidence: 76%
“…These findings on tree growth responses to climate are important since the Mediterranean area, as a transitional climate zone between humid and arid regions, is particularly sensitive to climate change (Mazza and Manetti 2013). However, in western Balkan, studies on climate-growth relationships of typical Mediterranean pine species are scarce (e.g., Sarris et al 2011;Toromani et al 2015a) and have not considered the early detection of forest dieback by means of cumulative scale drought indices as well as the drought impact on vegetation activity. This…”
Section: R a F Tmentioning
confidence: 99%
“…Therefore, water availability seems to be the most limiting factor for the species productivity in Spain, regardless of being within or outside the natural distribution of the species. Moreover, similar results were achieved by Rathgeber et al (2005) in Pinus halepensis stands in France, Klein et al (2014) and Maseyk et al (2011) in Israel andToromani et al (2015) in Albania, so this conclusion may be generalizable to the entire Mediterranean area.…”
Section: Site Index From Environmental Parameters In Pinus Halepensissupporting
confidence: 84%